PENERAPAN MODIFIKASI PERMAINAN DALAM PEMBELAJARAN DRIBBLING TERHADAP KETERAMPILAN MOTORIK TEKNIK DASAR DRIBBLING BOLA BASKET (STUDI PADA PESERTA DIDIK KELAS VII (TUJUH) DI SMP NEGERI 3 TUBAN) - NURWIDYAWATI, SHELVY (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract The purpose of this research is to determine whether there is an effect modification of the game against the results of motor skill learning the basic techniques of dribbling basketball. To determine how much influence modification against the learning outcomes of  basic motor skills dribbling of basketball techniques. Based on the findings of the study concluded that there are significant effects on the application of game modifications in teaching dribbling to the result of basic motor skills dribbling a basketball techniques  is proven by the t value 2.056 > 1.708 t value table. There is an increase in motor skills learning outcomes basketball dribbling basic techniques for 20.37% of the before and after treatment are given in the form of modifications in the learning dribbling basketball game. Keywords: Basic dribble movement, modifications, motor, learning